Sebuah PERANCANGAN SISTEM PENDATAAN ALAT KERJA DAN SARANAN KERJA (ALKER SARKER) PADA PT. TELKOM AKSES SORONG BERBASIS WEBSITE - Iriene Surya Rajagukguk (Electro Luceat, 2024)
Telkom Access is a company that focuses on the construction and management of network infrastructure services and is a subsidiary of Telkom. Alker Sarker is a work tool and work facility provided by the company to support technicians in carrying out physical repairs to network disturbances that occur in the field, the results of which are recorded via Excel or manually recorded in books. Sometimes data is lost and the manual notes that have been recorded are damaged every time an alker is checked sarker is caused by several ununtentional factors. This research aims to design a data collection system for work tools and work facilities (alker sarker) at PT. Telkom Sorong Access is website based. In this research, the data collection method uses observation, interviews and using the prototype method to develop the system. The website is prepared with a development stage procedure which includes analysis of user needs, then implementation using PHP as the programming language, MySql as the database and system testing with Black Box. From the research, a web-based work tool and work facility data collection system software was produced which has the ability to store goods stock data, as well as records related to the use of technicians' tools and reporting of goods to company leadership.